A synopsis of current practices in minimally invasive surgery for adult spinal deformity - Agrawal, Aniruddh V.; Agrawal, Vinod A.; Singhal, Adit A.; Maniar, Adit (International Journal of Research in Orthopaedics, 2017)
To provide a comprehensive summary of the status, indications and developments in the use of minimally invasive surgery in the field of adult spinal deformity. This study was performed by expert review of literature which has been published and is indexed on PubMed. The most appropriate and recent articles were selected to obtain a consolidation of information and knowledge on use and benefits of minimally invasive surgery in adult spinal deformity. Various MIS techniques have been developed to perform the complex ASD surgeries. These include the transforaminal lateral interbody fusion (TLIF), percutaneous segmental fixation as well as the lateral body interbody fusion (LLIF). It is important for a surgeon to obtain a holistic view of current literature and recommended guidelines on the procedures available for ASD surgeries. Overall, minimally invasive spine surgery has resulted in less use of pain medicine, less blood loss, lower infection rates, less requirement for intensive care, less hospitalization, reduction in physiologic stress, reduction in complication rates, reduction in muscle atrophy and preservation of normal motion with fusion rates being as high as 80-95%. More articles consolidating the vast literature on minimally invasive spine surgery need to be published to allow a surgeon to effectively weight the benefits and drawbacks of it. More research needs to be performed to compare the efficacy of sub-types of minimally invasive spine surgery.